2018
DOI: 10.1088/1361-6595/aad796
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive electrical asymmetry effect in an inductively coupled plasma reactor

Abstract: The electrical asymmetry effect is realized by applying multiple frequency power sources (13.56 MHz and 27.12 MHz) to a capacitively biased substrate electrode in a specific inductively coupled plasma reactor. On the one hand, by adjusting the phase angle θ between the multiple frequency power sources, an almost linear self-bias develops on the substrate electrode, and consequently the ion energy can be well modulated, while the ion flux stays constant within a large range of θ. On the other hand, the plasma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Based on the preceding assumptions, the field equations were derived through the direct summation and extrapolation of the particle motion equations. A standard MCC procedure was used [37][38][39][40][41][42][43][44] to calculate collisions, and the cross sections used in this study were adopted from references [37][38][39][40]. Because SEE is inevitable in gas discharge, the PIC-MCC model was self-consistently coupled with different emission models, including thermionic and SEE models, field and SEE models, and thermo-field and SEE models.…”
Section: Pic-mcc Simulation Resultsmentioning
confidence: 99%
“…Based on the preceding assumptions, the field equations were derived through the direct summation and extrapolation of the particle motion equations. A standard MCC procedure was used [37][38][39][40][41][42][43][44] to calculate collisions, and the cross sections used in this study were adopted from references [37][38][39][40]. Because SEE is inevitable in gas discharge, the PIC-MCC model was self-consistently coupled with different emission models, including thermionic and SEE models, field and SEE models, and thermo-field and SEE models.…”
Section: Pic-mcc Simulation Resultsmentioning
confidence: 99%
“…However, the investigation of the EAE in ICPs is very limited. Although Zhang and Bogaerts has already studied the EAE in inductively coupled C 4 F 8 /SF 6 plasmas and obtained similar conclusions as in CCPs [4], the effectiveness of the EAE on the independent modulation of the ion flux and ion energy in ICPs under various discharge conditions is not fully proved. Furthermore, the EAE is mainly investigated in electropositive or weakly electronegative CCPs, such as Ar, H 2 , H 2 /SiH 4 and O 2 discharges [35,[41][42][43][44][45][46][47][48], and the studies in strongly electronegative gases, such as Cl 2 , are rarely reported.…”
Section: Introductionmentioning
confidence: 98%
“…potential and thus the ion bombarding energy on the bottom electrode in ICPs is normally quite low, i.e. with maximum energy in the range between 20 eV and 40 eV, which limits the plasma processing efficiency [1,3,4]. Therefore, an idea of capacitive/inductive hybrid discharge is proposed, in which the plasma density and ion bombarding energy are controlled independently by the ICP power and capacitive bias power, respectively [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%